THE DETERMINANT FACTOR OF URINARY STONE FORMATION ON PALM OIL PROCESSING WORKERS AT PTPN VII BETUNG - Sukmawati, Sukmawati; Novrikasari, Novrikasari; Miksusanti, Miksusanti (BIOVALENTIA: Biological Research Journal, 2019)
High temperature of work environment affects fluid and electrolyte balance of workers. It is also affecting the urine production by increasing its concentration and if it lasts for a long time causes urinary crystallization. This work was aimed to analyze the determinant factor of urinary stone formation within palm processing workers at PTPN VII Betung. Population sample in this work is 103 workers which represents total population of workers at PTPN VII of Betung unit. Research was designed quantitatively using cross-sectional study. Data collection was carried out using several instruments i.e. questioner, interview and observation. The obtained data was processed through univariate, bivariate and multivariate analysis. Result shows the number of workers with a positive urinary crystallization are 18 workers (17.5%). Characteristic of respondent are typically aged < 45 years (68%), hydration status was not dehydrated (53.2%). Multiple logistic regression analysis result shows hydration status variable (OR = 5.508) affects the formation of urinary stone with worker’s age as confounder